ANALISIS BIOMASSA DAN CADANGAN KARBON PADA EKOSISTEM MANGROVE DESA MALANG RAPAT KABUPATEN BINTAN - Teguh Heriyanto; Bintal Amin (Berkala Perikanan Terubuk, 2017)
This research was conducted on April 2016 in the forest ecosystems in the conservation areas of Malang Rapat Village Bintan regency. Mangrove forest plays significant functions from the viewpoint of ecosystem services and climate change mitigation. The survey method was applied in this study and carbon stock analysis was carried out in the Marine Chemistry Laboratory, Faculty of Fisheries and Marine Science, Universitas Riau. The results showed that the highest biomass of mangrove was found in the trunk and followed by the root, branch and leaf with biomass values of 4477.81, 3326.10, 936.45 and 131.26 Kg respectively. The potential of the carbon biomass was also found in the trunk and followed by roots, branches and leaves with 2104.57, 1563.27, 440.13  and 61, 69 Kg respectively.The average value of carbon reserves in the mangrove conservation areas of Malang Rapat, Bintan Island was 4632.69 tons/Ha.